The Hidden World Of Changers : The Spirit Warrior - H. K. Varian (India Simon Spotlight, 2003)
Gabriella must master a mysterious new ability to save her friend in the sixth action-packed novel of The Hidden World of Changers series! Fiona, Mack, Gabriella, and Darren are Changers, a magical line of shapeshifters that can transform into mythological creatures, from werewolves and selkies to lightning birds and spirit foxes. The Changers are reeling from the attack at Wyndemere Academy. Their new enemy, Sakura Hiyamoto, is a kitsune with a unique memory-eating ability, and she$1 (Bs after Mack. Mack doesn$1 (Bt remember much about fighting Sakura at Wyndemere, a fact which worries the First Four deeply$1 (BSakura may have altered Mack$1 (Bs memories without him knowing$1 (Bor worse, he could secretly be under her control. With nowhere else to turn, the First Four ask Gabriella for help: As a nahual Changer, Gabriella can spirit walk into Mack$1 (Bs mind. But spirit walking is dangerous, and a power typically reserved for advanced Changers. To master her ability, Gabriella will need training and discipline. One false move, and her spirit could wander forever. Can she take control of this mysterious new power and save Mack?s
Keywords: Science Fiction